Towards a new education through AI: Didactic study of an intelligent platform - Hmissi, Wafa (American Journal of STEM Education, 2026)
In this study, we examine the impact of artificial intelligence on the teaching process–learning through an empirical investigation of a smart platform developed by university students as part of a project designed to support all learners, including those with autism. To identify the characteristics of this new form of so-called smart education, six semi-structured interviews were conducted with engineering students who created the integrated AI platform. The designers highlighted the benefits of personalized, automated education tailored to individual needs. This approach paves the way for an educational system in which technology helps to maintain motivation while redefining teacher roles. Finally, we present the results and highlight both the limitations of AI and those of the study itself.